HUBUNGAN INDEKS BRINKMAN DENGAN KADAR KOLESTEROL TOTAL PADA PASIEN HIPERTENSI YANG MEROKOK DI PUSKESMAS AMPLAS: THE RELATIONSHIP BETWEEN BRINKMAN INDEX AND TOTAL CHOLESTROL LEVELS OF HYPERTENSION PATIENS WHO SMOKE AT PUSKESMAS AMPLAS - Adelia, Salwa; Aktalina, Lucia; Hotmatua, Julahir Hodmatua; Sari, Siti Kemala (Fakultas Kedokteran Universitas Islam Sumatera Utara, 2026)
Hypertension in Indonesia contributes as the third cause of death reaching 6.8% of the entire death population in all age groups. The prevalence of hypertension is influenced by smoking habits. The chemical content of cigarettes such as nicotine can cause an increase in triglyceride levels, cholesterol, VLDL, and a decrease in HDL levels. Objective of this study is to analyze the relationship between the Brinkman index and total cholesterol levels in hypertensive patients who smoke at Puskesmas Amplas. Quantitative method with cross sectional approach with purposive sampling technique. The results of the analysis on 36 respondents using the somers'd test showed that there was a relationship between the Brinkman Index and Total Cholesterol Levels in Hypertensive Patients Who Smoke at Puskesmas Amplas (p value = 0.047). There is a relationship between the Brinkman Index and Total Cholesterol Levels in Hypertensive Patients who Smoke at the Amplas Health Center. AbstrakHipertensi di Indonesia berkontribusi sebagai penyebab kematian ketiga mencapai 6,8% dari seluruh populasi kematian di semua kelompok umur. Prevalensi kejadian hipertensi dipengaruhi kebiasaan merokok. Kandungan kimia rokok seperti nikotin dapat menyebabkan peningkatan kadar trigliserida, kolesterol, VLDL, serta penurunan kadar HDL. Tujuan penelitian ini untuk menganalisis hubungan antara indeks brinkman dengan kadar kolesterol total pada pasien hipertensi yang merokok di Puskesmas Amplas. Metode kuantitatif dengan pendekatan cross sectional dengan teknik pengambilan sampel purposive sampling. Hasil analisis pada 36 responden menggunakan uji somers’d menunjukkan bahwa terdapat hubungan antara Indeks Brinkman dengan Kadar Kolesterol Total pada Pasien Hipertensi yang Merokok di Puskesmas Amplas (nilai p = 0,047). Terdapat hubungan antara Indeks Brinkman dengan Kadar Kolesterol Total pada Pasien Hipertensi yang Merokok di Puskesmas Amplas.